Rancang Bangun Antena Mikrostrip Flower Patch with Circular Ring Frekuensi 2.4 GHz untuk Aplikasi Monitoring Ketinggian Air Toren Otomatis - Hayyina Wienastuti; Astri Astari; Yenniwarti Rafsyam (Politeknik Negeri Jakarta, 2025)
Microstrip Res are a popular type of antenna widely used in wireless communication systems due to their compact size, light weight, and ease of fabrication. This study focuses on the design and characterization of a flower patch microstrip antenna with combination circular ring element, operating at a frequency of 2.4 GHz for WiFi application. The design process was performed using full-wave electromagnetic simulation software to obtain optimum parameters, including return loss, Voltage Standing Wave Ratio (VSWR), and radiation pattern. Simulation results show the antenna achieved a return loss of 39.22 dB and a VSWR of 1.022, indicating good impedance matching to the 50 Ω system. The antenna was subsequently fabricated and tested using a Vector Network Analyzer (VNA) to verify the simulation results. The measurement results revealed an impedance value of 57.64 Ω, with a difference of approximately 7.6 Ω from the ideal value. This discrepancy is attributed to factors such as physical realization tolerance, dimensional variations, and fluctuations in the substrate's dielectric constant. Overall, the designed antenna exhibits good performance and shows potential for use as a WiFi antenna.